Breaking the vicious circle of escalating control: Connecting politicians and public employees through stewardship - Tina Øllgaard Bentzen (Administrative Sciences, 2021)
Politicians applying general rules as a reaction to local failures has contributed to mushrooming control in the public sector, which has in turn spurred higher transactional costs and motivation crowding among public employees. Drawing on a qualitative case study in a Danish municipality, this article explores the prospects and challenges for politicians of breaking the vicious circle of escalating control by adopting stewardship ideals into their leadership of the public employees. The results show that stewardship offers new opportunities for politicians, enabling better diagnosis of control problems, more robust control solutions, as well as a pronounced mobilization of employee support for those solutions. However, political competition, political discontinuity after elections, scandals in the press, resistance in the administration, and more diffuse decision-making processes pose potential challenges for politicians striving to tackle the problem of escalating control through stewardship.
Keywords: 350; agency theory; control; motivation crowding; political leadership; stewardship theory